Syringobulbia: A delayed complication following spinal cord injury – case report. (4th March 2019) - Mousele, Christina; Georgiopoulos, Miltiadis; Constantoyannis, Constantine
Abstract : Context: Syringobulbia is a very rare progressive disorder of central nervous system, with several possible underlying conditions. Rarely, it is also encountered as a late complication of syringomyelia. Findings: In the present manuscript, a case of a paraplegic patient, due to traumatic spinal cord injury (thoracolumbar fracture), presenting after years progressively developing symptoms of the lower cranial nerves and upper extremities, owed to syringomyelia and syringobulbia, the surgical treatment applied and its outcomes are described. We performed a syringo-peritoneal shunting procedure using a T-tube. The patient's symptoms resolved postoperatively and the cavity's size was reduced to a great degree. Conclusion/Clinical Relevance: The late appearance of cranial nerve deficits or symptoms—signs of the upper extremities in a patient with traumatic thoracic spinal cord injury should raise suspicion that post-traumatic syringomyelia or syringobulbia has occurred. In such cases, radiologic evaluation and early surgical drainage of the cyst as a means of preventing significant delayed neurologic deficit is advocated.